MODELING THE PROBLEM OF FORCED OSCILLATIONS OF A DAM-PLATE WITH CONSTANT AND VARIABLE STIFFNESS, TAKING INTO ACCOUNT THE VISCOELASTIC PROPERTIES OF THE MATERIAL AND HYDRODYNAMIC WATER PRESSURES (American Journal of Technology and Applied Sciences, 2022)
In this article highlights of modeling the problem of forced oscillations of a dam-plate with constant and variable stiffness, taking into account the viscoelastic properties of the material and hydrodynamic water pressures.